Frequency of toothbrushing in children under 12 years old in Peru, 2019 2021 - Karen Cabanillas-Yllesca; Roberto Antonio León-Manco; César Eduardo Del Castillo-López; María Claudia Garcés-Elías (Universidad de Antioquia, 2024)
Introduction: dental caries is caused by poor oral hygiene, so it is necessary to have adequate hygiene. The objective of the study was to determine the practice of toothbrushing in Peruvian children under 12 years of age between 2019 and 2021. Methods: a cross sectional, analytical, and retrospective analysis was used by applying the 2019,2020 and 2021 Demographic and Family Health Survey databases. 38 203 records were obtained in 2019, 18 613 in 2020, and 35 759 in 2021. The variables were general, daily , and minimum two times a day toothbrushing, natural region, area and place of residence, altitude, wealth index, health insurance coverage, age, and sex. A descriptive, bivariate, and multivariate statistical evaluation was carried out. Results: t hat gene ral toothbrushing was 94.93% (n=83,032), daily toothbrushing was 86.32% (n=67,753), and at least twice a day was 82.93% (n=53,824). In multivariate form, the year 2020 showed a negative association with daily toothbrushing (RPa: 0.97; 95% CI: 0.96 0.99; p< 0.001) and at least twice a day (RPa: 0.96; 95% CI: 0.95 0.98; p<0.001). The year 2021 revealed a negative association with general toothbrushing (RPa:0.98; 95%CI: 0.97 0.98; p<0.001), daily (RPa:0.97; 95%CI: 0.95 0.98; p<0.001) and minimum twice a day (RP a: 0.94; 95%CI: 0.92 0.96; p<0.001), adjusted for the previously associated covariates. Conclusions: t he studied years were negatively associated with general toothbrushing, daily toothbrushing, and toothbrushing minimum twice daily.